2004
DOI: 10.1016/j.jclinepi.2004.01.019
|View full text |Cite
|
Sign up to set email alerts
|

A nested case-control study of influenza vaccination was a cost-effective alternative to a full cohort analysis

Abstract: Objective: In the absence of trial results that are applicable to the target population, nested case-control studies might be an alternative to full-cohort analysis. We compared relative and absolute estimates of associations in an influenza vaccine study using both designs.Study Design and Setting: Data from elderly persons enrolled during six consecutive influenza seasons were used (147,551 personperiods). The endpoints "hospitalization for pneumonia or influenza" (P&I) or "death" were used combined and sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Previously, we have demonstrated that a nested casecontrol approach is an efficient alternative to full-cohort analysis for the study of influenza vaccination (14). The PRISMA study was conducted in 91 general practices during the 1999 -2000 influenza A epidemic and during two consecutive seasons in which the influenza activity ap For the purpose of our study, we therefore choose to analyze the data of case and control subjects ascertained from the primary care-based cohort of 75,235 study patients of any age followed up during the…”
Section: Research Design and Methods -mentioning
confidence: 99%
“…Previously, we have demonstrated that a nested casecontrol approach is an efficient alternative to full-cohort analysis for the study of influenza vaccination (14). The PRISMA study was conducted in 91 general practices during the 1999 -2000 influenza A epidemic and during two consecutive seasons in which the influenza activity ap For the purpose of our study, we therefore choose to analyze the data of case and control subjects ascertained from the primary care-based cohort of 75,235 study patients of any age followed up during the…”
Section: Research Design and Methods -mentioning
confidence: 99%
“…Thus, the actual unit of analysis is the migration. Generalizing from person-periods to individuals is allowable if each event is independent and standard errors do not change substantially when individuals, rather than person-periods, are analyzed (Hak et al 2004;Preston et al 2001). The conclusions are robust when results persist in multivariate analyses since the procedure controls for the effect of some individuals contributing more person-periods than others.…”
Section: Measuring Migrationsmentioning
confidence: 99%
“…This is especially applicable for influenza vaccine effectiveness studies [16,17]. In fact, only one randomized controlled trial has been performed on the effectiveness of influenza vaccination in reducing influenza infection among healthy elderly persons [11].…”
Section: Introductionmentioning
confidence: 99%